Multivariate Cointegration Analysis and the Long-Run Validity of PPP - Kugler, Peter; Lenz, Carlos (The Review of Economics and Statistics, 1993)
This paper tests the long-run validity of PPP using Johansen's multivariate cointegration methodology on exchange rates and domestic and foreign price levels. Monthly data covering the recent flexible exchange rate period of the DM vis a vis 15 currencies le ad to the following conclusion: PPP seems to hold in the long run for s ix European currencies: the Pound, Lira, Norwegian Krone, Schilling, Escudo, and Peseta. However, PPP has to be rejected.for the United States and the Canadian Dollar as well as for the Belgian Franc and the Danish Krone. Nevertheless, the authors' analysis is more favorable to PPP as a long-run property of exchange rates than the recent work applying the Engle/Granger regression methodology. Copyright 1993 by MIT Press.